2016
DOI: 10.3171/2015.1.jns14408
|View full text |Cite
|
Sign up to set email alerts
|

Laser speckle imaging to improve clinical outcomes for patients with trigeminal neuralgia undergoing radiofrequency thermocoagulation

Abstract: Noninvasive laser speckle imaging can be performed safely in nonhuman primates. Because improved probe placement may reduce morbidity associated with percutaneous rhizotomies, efficacy trials of laser speckle imaging should be conducted in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…LSCI has become a valuable and powerful tool to investigate the fast change in microcirculation blood flow because of safety, wide measurement range, good reliability, high stability, and strong practicability. [37][38][39][40] Patient populations, such as those with peripheral vascular disease, those receiving vasodilator drugs prior to surgery, or those with infected toenails might have altered the BFI values and thus require separate determination.…”
Section: Discussionmentioning
confidence: 99%
“…LSCI has become a valuable and powerful tool to investigate the fast change in microcirculation blood flow because of safety, wide measurement range, good reliability, high stability, and strong practicability. [37][38][39][40] Patient populations, such as those with peripheral vascular disease, those receiving vasodilator drugs prior to surgery, or those with infected toenails might have altered the BFI values and thus require separate determination.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed the blood flow/perfusion around targeted muscles could be measured by using LSCI, so that the muscle microcirculation could be analyzed [ 20 , 21 ]. The LSCI also showed some good findings for assessment of pain-related blood perfusion [ 22 , 23 ]. Thus, the LSCI would be an additional way to reveal the mechanism of HSP.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TTFM cannot map the spatial distribution of the blood flow velocity. Since LSCI has been widely attempted in many clinical and biomedical applications during recent years [14][15][16], the LSCI technology is promising to detect the flow of the CA and has not been reported. In this study, to obtain a more accurate assessment of the pulsatile flow of the CA, we developed a speckle triangle assessment using the LSCI model: the speckle flow index (SFI), mean flow index (MFI), and pulsatility index (PI).…”
Section: Introductionmentioning
confidence: 99%